Assignment model approach for planning and allocating government tenders / Muhammad Hafiz Abd Hamid - Abd Hamid, Muhammad Hafiz (Universiti Teknologi MARA, Perlis, 2019)
In this research, the concept of assignment problem was applied to solve a problem for government department (Jabatan Kerja Raya Perak) which had difficulty is assigning six different tender projects to six different contractors. In this research, tenders projects called as 1, 2, 3, 4, 5 and 6 while contractors called as A, B, C, D. E and F. Based on the data collected, an assignment method known as Hungarian Method was used to solve the problem in obtaining optimal solution. Optimal assignments of the tender projects to the contractors were obtained for the Jabatan Kerja Raya Perak. The results showed that tender projects 1, 2, 3, 4, 5 and 6 should be assigned to contractors F, A, D, B, C and E respectively. The research find that the total optimal cost to be expended on all tender projects was RM 15,040,000 which was lesser than the actual cost.